MULTIFUNCTIONAL AGRICULTURE AS AN INNOVATION PATH FOR RURAL AREAS - Madureira, Lívia; Susete, Costa (Economics of Agriculture, 2018)
The main purpose of this paper is to discuss the potential of MFA model to enhance innovation in rural areas build on the analysis of information from a database of best practices on innovation in EU rural areas collected by the RAPIDO project3. The analysis shows innovation to be strongly related to multiple-activity. This suggests the synergies between functions and land-uses to overlap the competition for resources between activities and that MFA shows a promising approach to enhance innovation in rural areas.